2008
DOI: 10.4049/jimmunol.180.4.2039
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: CD4 T Cell-Mast Cell Interactions Alter IgE Receptor Expression and Signaling

Abstract: Mast cell activation is associated with atopic and inflammatory diseases, but the natural controls of mast cell homeostasis are poorly understood. We hypothesized that CD4+CD25+ regulatory T cells (Treg) could function in mast cell homeostasis. In this study, we demonstrate that mast cells can recruit both Treg and conventional CD4+ T cells (Tconv). Furthermore, Treg, but not Tconv, suppress mast cell FcεRI expression. Despite the known inhibitory functions of IL-10 and TGFβ1, FcεRI suppression was independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 33 publications
2
67
0
2
Order By: Relevance
“…Since Treg normally suppress inflammation, one cannot rule out the possibility that depletion of Treg will escalate inflammation and accelerate progression of CRC. MC are known to recruit Treg (35), to mediate Treg suppression of host-vs-graft rejection responses (7), and we have now demonstrated that they can also render the Treg proinflammatory. We predict that a safer therapeutic strategy in CRC may be to target the Treg and MC interaction to hinder the generation of ΔTreg.…”
Section: Mc-mediated Diversion Of Treg To Proinflammatory Phenotype Doesmentioning
confidence: 93%
“…Since Treg normally suppress inflammation, one cannot rule out the possibility that depletion of Treg will escalate inflammation and accelerate progression of CRC. MC are known to recruit Treg (35), to mediate Treg suppression of host-vs-graft rejection responses (7), and we have now demonstrated that they can also render the Treg proinflammatory. We predict that a safer therapeutic strategy in CRC may be to target the Treg and MC interaction to hinder the generation of ΔTreg.…”
Section: Mc-mediated Diversion Of Treg To Proinflammatory Phenotype Doesmentioning
confidence: 93%
“…On the same line, some of us have recently found that histamine might protect from EAE because mice unable to synthesize histamine because of a genetic deficit in the histidine decarboxylase develop exacerbated disease on MOG immunization. 33 A recent report shows Tregs inhibiting Fc⑀RI expression in MC, 34 a process that may result in the impairment of certain MC functions and, as a consequence, in altered T-cell activation. However, we could not find any difference in Fc⑀RI expression on MC, in coculture with or without Tregs (not shown), or in Treg-depleted or replete animals in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…15 Tregs have been shown to broadly suppress activation, proliferation, and/or effector functions of various immune cell populations such as conventional CD4 ϩ and CD8 ϩ T cells, 16 natural killer (NK) T cells, 17 B cells, 18 dendritic cells, 19 monocytes/macrophages, 20 neutrophils, 21 and mast cells. 22 Depletion of CD4 ϩ CD25 ϩ T cells induces effective antitumor immunity, enhances immune responses to invading microbes, triggers allergic responses to innocuous environmental substances, and breaks fetus-maternal tolerance during pregnancy. 11 On the other hand, Tregs have been found to suppress several T cellmediated immune pathologies, including allergic responses and autoimmune diseases such as type 1 diabetes (T1D), experimental autoimmune encephalomyelitis (EAE), gastritis, colitis, glomerulonephritis, and polyarthritis as well as allograft rejection and graft-versus-host disease (GVHD).…”
Section: Introductionmentioning
confidence: 99%